Controllable reconstruction of copper nanowires into nanotubes for efficient electrocatalytic nitrate conversion into ammonia. Issue 34 (15th August 2022) - Li, Chunjie; Liu, Songliang; Xu, You; Ren, Tianlun; Guo, Yanan; Wang, Ziqiang; Li, Xiaonian; Wang, Liang; Wang, Hongjing
Abstract : Hierarchical nanosheet-based Cu nanotubes were prepared and their enhanced electrocatalytic activity and high selectivity for nitrate reduction to ammonia are demonstrated. Abstract : The electrochemical reduction of nitrate to ammonia provides a green and delocalized route for ammonia synthesis under ambient conditions, which requires advanced catalysts with high activity and selectivity. In this work, we propose a two-step conversion strategy to construct hierarchical copper nanosheet-based Cu nanotubes using pre-synthesized Cu nanowires as the starting material for the electrocatalytic nitrate reduction reaction (NO3 RR). The conversion of Cu nanowires into Cu nanotubes could be realized through chemical oxidation followed by in situ electrochemical reduction, enabling the effective engineering of active sites and thus boosting the electrocatalytic nitrate-to-ammonia capability. Such a controllable reconstruction strategy provides a new avenue for constructing high-performance electrocatalysts for sustainable NH3 synthesis and the elimination of NO3 − contamination.